Tales from Perrault - Lawrence, Ann; Lawrence, Ann 1942-; Chance, Tony James (Oxford : Oxford University Press, 1988)
An anthology of eleven classic tales form Perrault.
8 - 10 years
Keywords: Perrault, Charles; Fairy Tales -- Juvenile Literature